Use of pectin in patients with diabetes mellitus type 2 in the complex treatment of the periodontal disease (report 1) - Kosenko, S. V.; Balaban, I. O.; Hayoshko, O. B.; Ilnytska, O. M.; Yatsynovych, N. M.; Ivanov, S. O.; Muzichenko, N. I. (Zaporozhye Medical Journal, 2014)
Aim. This study submits technology of treatment the chronic generalized periodontitis of II–III degree in patients with diabetes mellitus type II. Methods and results. The results demonstrate that endogenous and exogenous application of pectin preparation «Pektodent» (Ukraine) as a hygienic and preventive medication «Pektodent» (dentifrice), the shape-forming recipe for retention of «Pektodent» (for bandages) and a recipe for oral use can reduce the aggressiveness periodontitis at diabetes in the period of rehabilitation. Conclusion. Evidence-based approach allows positively resolve problematic situation. Result of rehabilitation period depends on patient discipline.